Sistem Pemantauan dan Pengawasan Keamanan Siswa Berbasis Wearable IoT di Lingkungan Sekolah Madrasah Ibtidaiyah - Aqmal Fahat Syafiq Putra; Eka Arriyanti; Kusnandar Kusnandar (TIN: Terapan Informatika Nusantara, 2026)
Student safety within school environments remains a critical concern, as manual supervision is constrained in its capacity to monitor students’ whereabouts and conditions rapidly and continuously. This study contributes by providing a technology-based medium that integrates IoT-enabled wearable devices, real-time data communication, and a centralized monitoring dashboard to strengthen school surveillance systems, while simultaneously addressing a gap in the literature concerning the implementation of wearable IoT in the context of Indonesian madrasah ibtidaiyah (elementary Islamic schools). The study aims to design and develop a wearable IoT-based student safety monitoring and supervision system capable of tracking students’ locations and basic physiological conditions in real time and transmitting emergency notifications to school authorities. The research was conducted at MI Al Azhar, Samarinda, East Kalimantan, from 20 July to 25 August 2026, involving six respondents: one principal, one teacher, one student affairs coordinator, one school IT technician, and two sixth-grade students. A Research and Development (R&D) approach employing a prototype model was utilized, encompassing stages of needs analysis, design, implementation, testing, and evaluation. Findings indicate that the system is capable of monitoring students’ conditions and whereabouts in real time, detecting potential risks via wearable devices, displaying movement histories and student status on a dashboard, and delivering emergency notifications more rapidly. The system also demonstrably enhances the effectiveness of student safety supervision in schools, as information can be monitored centrally and responses to incidents become more targeted. Based on testing outcomes and respondent feedback, the system is deemed feasible for use as an innovative solution to support student safety within school environments. The study’s contributions include the provision of an adaptable wearable IoT implementation framework for other schools, the strengthening of the empirical basis regarding the effectiveness of student monitoring systems at the elementary level, and the formulation of technical design recommendations and operational policies to support scalability and secure data governance.